1990
DOI: 10.5980/jpnjurol1989.81.1255
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Medullary Sponge Disease Associated With Horseshoe Kidney

Abstract: A 60-year-old man visited our hospital with complaints of micturition pain and interruption of urinary stream. X-ray examinations were performed, showing no bladder and urethral stone. However, KUB revealed bilateral multiple renal stones. Excretory urography showed a horseshoe kidney and a concentration of the contrast medium in the ectatic tubules at the pyramidal apices. Calculi were also located in these ectatic tubules. Thus, we considered that this was a very rare case of medullary sponge disease associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…[ 14 18 19 20 21 22 ] Second, previous studies have demonstrated that metabolic factors including hyperparathyroidism, low urine volumes, hypercalciuria, hyperoxaluria, hyperuricosuria, and hypocitraturia[ 15 18 23 24 25 ] are common in patients with HSK, which may contribute to higher stone formation. Third, the previous reports have demonstrated coexistent HSK with medullary sponge kidney,[ 40 41 42 ] a known cause of stone disease. [ 43 ]…”
Section: Discussionmentioning
confidence: 97%
“…[ 14 18 19 20 21 22 ] Second, previous studies have demonstrated that metabolic factors including hyperparathyroidism, low urine volumes, hypercalciuria, hyperoxaluria, hyperuricosuria, and hypocitraturia[ 15 18 23 24 25 ] are common in patients with HSK, which may contribute to higher stone formation. Third, the previous reports have demonstrated coexistent HSK with medullary sponge kidney,[ 40 41 42 ] a known cause of stone disease. [ 43 ]…”
Section: Discussionmentioning
confidence: 97%
“…[45] Since MSK can be simply missed because intravenous urography is not used as often as it used for the investigations for kidney stones,[67] physicians should be aware of this potential coexistence and future study is warranted.…”
mentioning
confidence: 99%